The use of the rotary converter in substations - Graham, Lewis M.; Elder, Leonard Roscoe (My University, 1906)
Introduction: In street or interurban railway service, when the distance from the central station becomes greater than five or six miles, the copper losses over the trolley become excessive, and it is necessary to reduce these losses to a minimum. This is done by generating alternating current at from 2000 to 7000 volts, or if a higher voltage is desired a step up transformer is used. This high potential is transmitted to a substation situated at some convenient place on the line. Here the line voltage is stepped down by a transformer to something below 1100 and converted into direct current. This conversion may be made by one of three ways. (1). The alternating current may be fed into a synchronous or induction motor which is belted or direct connected to a direct current generator. (2). A motor-generator may be used. This is a machine with two separate armature windings on the same core, one being connected to slip rings through which alternating current is fed and operates the machine as a synchronous motor, driving the other winding as a direct current generator connected to a commutator. (3). The alternating current may be fed into a rotary converter, direct current being taken off at the other end. It is about this machine that I wish to write. The rotary converter as far as purpose is concerned is simply the commutator of a direct current rotating at some distance from the generator. But with it as with any commutator it must rotate at the same cyclic speed as the generator. To accomplish this the principle of the synchronous motor is used, for the synchronous motor will run at synchronous speed if it runs at all. So the rotary converter is essentially a synchronous motor in the respect that it has a magnetic field in which rotates an armature winding connected slip rings by leads which are taped on at regular intervals, there being as many rings as there are phases in the circuit.
Citation: Graham, Lewis M. Elder, Leonard Roscoe. The use of the rotary converter in substations. Senior thesis, Kansas State Agricultural College, 1906.
Morse Department of Special Collections
Keywords: Mechanical Engineering; Rotary Converter; Synchronous Motor; Railroad; Substation; Electricity; Theses